The regulatory role of the circELMOD3-associated ceRNA network in the progression and prognosis of hepatocellular carcinoma - Li, Deyuan; Liu, Meiliang; Lai, Mingshuang; Wang, Lijun; Wei, Liling; Wu, Siqian; Liang, Si; Liu, Shun; Zeng, Xiaoyun (Frontiers in Genetics, 2025)
BackgroundOur previously research has validated the effect of circELMOD3 on HCC tumor inhibition. However, further investigations are warranted to investigate the prognostic significance of circELMOD3 in HCC and its regulation via the competitive endogenous RNA (ceRNA) network.MethodsThe gene expression profiles and clinical information were obtained from The Cancer Genome Atlas (TCGA-LIHC) and International Cancer Genome Consortium (ICGC). Base on the circMine, miRWalk and TargetScan database, we constructed circELMOD3-miRNA-mRNA network. Univariate Cox and least absolute shrinkage and selection operator (LASSO) regression analysis was used to constructed the prognostic model. Additionally, Gene set enrichment analysis (GSEA) was conducted for the prognostic-related genes. Finally, the expression levels of genes and proteins were respectively assessed by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting.ResultsWe constructed a ceRNA network comprising circELMOD3, 5 miRNAs, and 274 mRNAs. From this ceRNA network, we identified four prognostication-relation genes to develop a survival prediction model. In the TCGA-LIHC training set, the area under the curve (AUC) values for one-, three- and five-years of survival were 0.734, 0.718 and 0.707, respectively, then we validated the prognostic model in International Cancer Genome Consortium database. Gene set enrichment analysis displayed that these four prognostic genes were primary enriched pathways related to cell cycle regulation. Our finding demonstrated that circELMOD3 could affect the relative expression levels of N-cadherin, E-cadherin, CDK4, CDK6 and CyclinD1 proteins.Conclusionwe constructed a novel ceRNA network based on circELMOD3, to comprehensively characterizing the prognosis of HCC, providing valuable insights for the therapy and prognosis of HCC.